A rare radiological image of liver hydatidosis - Rosa, Folco; Fontán, Walter (Cirugía del Uruguay, 2020)
A case of a female child aged 10 suffering from hepatic hydatid disease is reported. Radiologic examination of right hypocondrium shows severa! intrahepatic nodules. Surgical management artd pathologic anatomy proved that they were hydat cysts.